Elazığ İlinde Bulunan Çocuklarda Dental Anomali Görülme Prevalansı - Daldal, Merve; Baybars, Sümeyye Coşgun; Ok, Elif (Dicle Üniversitesi, 2023)
Amaç: Bu çalışmada, Ağız, Diş ve Çene Radyolojisi Anabilim Dalı’na çeşitli sebeplerle başvuran, 5-14 yaş grubu 1500 hastanın Ortopantomografi görüntüleri retrospektif tarama ile incelenmiştir. Hastaların daimi kesici ve azı dişlerindeki; sürnümerer diş, taurodont diş, diş eksikliği, kama lateral, füzyon ve geminasyon varlığının değerlendirilmesi amaçlanmıştır. Gereç ve Yöntem: Panoramik radyograflarda belirlenen konjenital diş eksiklikleri, sürnümerer dişler, taurodontizm, füzyon, geminasyon, kama lateral dişler hastanın yaş, cinsiyet, lokalizasyon, sayı ve morfolojilerine göre değerlendirildi. Bulgular: Dental anomali tespit edilen hastaların, %3,7 sinde diş eksikliği, %0,8 sinde sürnümerer diş, %9,7 sinde taurodontizm, %2,7 ünde kama lateral, sadece bir hastada füzyon   görülürken geminasyonu olan hastaya rastlanmadı. Cinsiyetler arasında dental anomalilerin her birinin görülme oranlarında istatistiksel açıdan anlamlı bir farklılık bulunmadı (p>0,05) Ancak yaş grupları arasında 10-14 yaş grubunda dental anomali görülme oranı (%44,7), anlamlı derecede diğer yaş gruplarından yüksek tespit edildi (p

Aim: In this study, Orthopantomography images of 1500 patients aged 5-14 years who applied to the Department of Oral and Maxillofacial Radiology for various reasons were examined by retrospective scanning. In patients’ permanent incisors and molars, It is aimed to evaluate the presence of supernumerary teeth, taurodont teeth, missing teeth, wedge lateral, fusion, and gemination. Material and Method: Congenital tooth deficiencies, supernumerary teeth, taurodontism, fusion, gemination, and wedge lateral teeth identified on panoramic radiographs were evaluated according to the patient’s age, gender, localization, number, and morphology. Results: Among the patients with dental anomalies, missing teeth were observed in 3.7%, supernumerary teeth in 0.8%, taurodontism in 9.7%, lateral wedge in 2.7%, fusion was observed in only one patient, and no patient with gemination was observed. There was no statistically significant difference in the incidence rates of each dental anomaly between genders (p>0.05). However, among the age groups, the incidence of dental anomalies in the 10-14 age group (44.7%) was significantly higher than the other age groups (p
Prevalence of Dental Anomaly in Children in Elazığ Province
Keywords: Oral and Maxillofacial Radiology; Ağız; Diş ve Çene Radyolojisi